Genome-Wide Analysis of H3K27me3 in Porcine Embryonic Muscle Development - Tan, Baohua; Wang, Sheng; Wang, Shanshan; Zeng, Jiekang; Hong, Linjun; Li, Zicong; Yang, Jie; Cai, Gengyuan; Zheng, Enqin; Wu, Zhenfang; Gu, Ting (Frontiers in Cell and Developmental Biology, 2021)
The trimethylation of histone H3 lysine 27 (H3K27me3) is one of the most important chromatin modifications, which generally present as a repressive mark in various biological processes. However, the dynamic and global-scale distribution of H3K27me3 during porcine embryonic muscle development remains unclear. Here, we provided a comprehensive genome-wide view of H3K27me3 and analyzed the matching transcriptome in the skeletal muscle on days 33, 65, 90 post-coitus from Duroc fetuses. Transcriptome analysis identified 4124 different expressed genes (DEGs) and revealed the key transcriptional properties in three stages. We found that the global H3K27me3 levels continually increased during embryonic development and H3K27me3 level was negative with gene expression. The loss of H3K27me3 in the promoter was associated with the transcriptional activation of 856 DEGs in various processes, including skeletal muscle development, calcium signaling and multiple metabolic pathways. Lastly, we identified for the first time that H3K27me3 could enrich in the promoter of the genes, such as DES, MYH7, TNNC1 and KLF5, to negatively regulate gene expression in porcine skeletal muscle satellite cells (PSCs), which demonstrated the repression function of H3K27me3 for muscle cell differentiation. Taken together, this study provided the first genome-wide landscape of H3K27me3 in porcine embryonic muscle development. It revealed the complex and broad function of H3K27me3 in the regulation of embryonic muscle development from skeletal muscle morphogenesis to myofiber maturation.